SWOT Analysis in Formulating Competitive Strategies at the Property Company PT Green Dramaga, Bogor City - Dyah Oktabriawatie Waluyani; Ira Caharina Kaban; Priscilla Gareen Ariesta; Veronica Lusianna Sitohang; Masno Marjohan (Indonesian Development of Economics and Administration Journal, 2024)
This study aims to analyze and formulate a competitive strategy for PT Green Dramaga so that the company can survive and win the competition in the market. The type of research used is qualitative with Observation, Interview and Documentation techniques. The study was conducted by analyzing the internal environment through Resource Based View and external analysis through Porter's five forces, which were then analyzed using SWOT analysis so that it would produce a strategy that is in accordance with the type of strategy that exists. From the results of the study, the researcher found that the right competitive strategy to be implemented by PT Green Dramaga is a strategic product and place strategy. Regularity, novelty and complexity are three important factors in the quality of housing design. The location of PT Green Dramaga housing which deliberately chooses a strategic housing location close to community activities such as in the school environment, campus, market and where the community works.